Aspectos morfológicos comparativos entre neurônios da camada I do córtex visual de duas espécies de roedores: Cavia porcellus e Rattus norvegicus - MOREIRA, Thayana de Nazaré Araújo (Universidade Federal do Pará, 2014)
The layer I has as main characteristic the low number of neurons and a high density of nerve fibers. The morphology of neurons of layer I is still understudied, so that in studies evaluating the morphology of these neurons has not yet reached a consensus on the forms and functions of these neurons. This study evaluated the morphology of neurons in layer I of the visual cortex of two rodent species: Cavia porcellus, popularly known in Brazil as a guinea pig and Rattus norvegicus, which is the rat and the Wistar strain was used, commonly used in scientific research. The guinea pig is a widely studied animal model used in several areas of science. Although this species is well studied, works on layer I of this animal are relatively rare, especially in relation to morphology and electrophysiology of neurons in this cortical region. Research in rats on neurons of layer I are more frequent, both in relation to morphology and electrophysiology. To discriminate the potential for differences in the morphology of neurons in layer I of the visual cortex of the guinea pig and mouse, this study classified these neurons according to the trajectory of their dendrites and dendritic measures analyzed using the technique of intracellular injection of biocytin. After classification of neurons comparisons were made between the same cell types of each rodent. 35 guinea India Dunkin-Hartley variety of short-haired of both sexes aged 4-5 days of postnatal life were used. As for the rats, 30 rats of Wistar variety of both sexes aged 14 to 21 days of postnatal life were used. The animals were anesthetized and had their brains removed, separated hemispheres and sections were made in the coronal plane in the occipital region where is located the visual area of rodents. Slices were maintained in artificial cerebrospinal fluid and then brought to the microscope to inject biocytin and subsequently were fixed and treated for mounting on slides and counterstained with Nissl for better viewing. Neurons found were classified as horizontal, ascending, descending and radial. The receptive field area, total and average dendritic length, total area of the cell body, dendrites number, distance from the pia mater and distribution analysis Sholl: The following dendritic measures were analyzed. Results of the most notable were the extent of dendritic branches and the size of the cell body of neurons of layer I of the guinea pig compared to rat. This suggests that in this species, a larger number of neural microcircuits can be established, and therefore greater metabolic rate justified by the size of the cell body.